Wetlands and Water Framework Directive - Ignar, Stefan; Grygoruk, Mateusz (GeoPlanet: Earth and Planetary Sciences, 2015)
Environmental Science and Engineering; Water Policy/Water Governance/Water Management; Geoecology/Natural Processes